92.8k views
5 votes
HELP IT'S DUE IN 18 MINUTES!

HELP IT'S DUE IN 18 MINUTES!-example-1
User Hemantsb
by
5.0k points

1 Answer

2 votes

Answer:

Please check the explanation!

Explanation:

As the discrimination expression is


b^2-4ac

if


b^2-4ac\:<0

then the equation has no real solution.

Given the equation


mx^2+3x+1-m=0

by comparing the quadratic equation


\:ax^2+bx+c=0


mx^2+3x+1-m=0

we can observe that


a=m


b=3


c=(1-m)

substituting the values in discrimination to find the values of m

so


3^2-4m\left(1-m\right)=0


9-4m+4m^2=0


4m^2-4m+9=0


(-4m+4m^2)/(4)=(-9)/(4)


-m+m^2=-(9)/(4)


\left(m-(1)/(2)\right)^2=-2

as


\mathrm{For\:}f^2\left(x\right)=a\mathrm{\:the\:solutions\:are\:}f\left(x\right)=√(a),\:-√(a)

so solving


m-(1)/(2)=√(-2)


m-(1)/(2)=√(-1)√(2)


m-(1)/(2)=√(2)i
√(-1)=i


m=√(2)i+(1)/(2)

and also solving


m-(1)/(2)=-√(-2)


m-(1)/(2)=-√(2)i


m=-√(2)i+(1)/(2)

As we know that

if


b^2-4ac\:<0

then the equation has no real solution.

Therefore, for the values of
m=√(2)i+(1)/(2),\:m=-√(2)i+(1)/(2), for which the equation
mx^2+3x+1-m=0 will have no solution.

User Richard Bos
by
5.1k points